Photonic properties of titania inverse opal heterostructures - Lee, Hooi Sing; Kubrin, Roman; Zierold, Robert; Petrov, Alexander Yu; Nielsch, Kornelius; Schneider, Gerold A.; Eich, Manfred (Optical Materials Express, 2013)
Titania inverse opal heterostructures demonstrating two distinctive photonic stopgaps were fabricated by repetitive vertical selfassembly and atomic layer deposition (ALD). Angle resolved reflectance measurements of the inverse opal heterostructure are reported for the first time. The comparison with the spectra of constituents show that the GL stopgaps of the heterostructure obey the superposition principle and the angular dispersion of their stopgaps is well-fitted with the modified Bragg's law at low incidence angles. Numerical simulations were used to predict the dominant features in the reflectance spectra. The total (specular and diffuse) transmission and reflectance measurements of the single inverse opals and the heterostructure reveal that the diffuse scattering could severely impair the photonic properties of the buried layers in the multi-stack photonic crystal (PhC) configurations. Ascending stacking is proposed as a means to improve the performance of the multi-layer coatings. © 2013 Optical Society of America.
CRIS-Team Scopus Importer:2023-03-20